Presence of the knockdown resistance mutation, Vgsc-1014F in Anopheles gambiae and An. arabiensis in western Kenya. Issue 1 (December 2015) - Ochomo, Eric; Subramaniam, Krishanthi; Kemei, Brigid; Rippon, Emily; Bayoh, Nabie; Kamau, Luna; Atieli, Francis; Vulule, John; Ouma, Collins; Gimnig, John; Donnelly, Martin; Mbogo, Charles
Abstract Introduction The voltage gated sodium channel mutationVgsc-1014S (kdr -east) was first reported in Kenya in 2000 and has since been observed to occur at high frequencies in the localAnopheles gambiae s.s. population. The mutationVgsc-1014F has never been reported fromAn. gambiae Complex complex mosquitoes in Kenya. Findings Molecularly confirmedAn. gambiae s.s. (hereafterAn. gambiae ) andAn. arabiensis collected from 4 different parts of western Kenya were genotyped forkdr from 2011 to 2013.Vgsc-1014F was observed to have emerged, apparently, simultaneously in bothAn. gambiae andAn. arabiensis in 2012. A portion of the samples were submitted for sequencing in order to confirm theVgsc-1014F genotyping results. The resulting sequence data were deposited in GenBank (Accession numbers: KR867642-KR867651, KT758295-KT758303). A singleVgsc -1014F haplotype was observed suggesting, a common origin in both species. Conclusion This is the first report ofVgsc-1014F in Kenya. Based on our samples, the mutation is present in low frequencies in bothAn. gambiae andAn. arabiensis . It is important that we start monitoring relative frequencies of the twokdr genes so that we can determine their relative importance in an area of high insecticide treated net ownership.